2022
DOI: 10.3389/fphar.2022.1039558
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate Mo nanoparticles (EGM NPs) efficiently treat liver injury by strongly reducing oxidative stress, inflammation and endoplasmic reticulum stress

Abstract: Drug-induced liver injury (DILI) is a serious clinical disease associated with reactive oxygen species (ROS) burst and subsequent inflammatory responses. However, traditional treatments were limited by low efficacy and serious side effects due to the special liver structure. Here, we developed a molybdenum (Mo)-based nanoparticles, EGM NPs, after overall consideration of the pathophysiology of DILI and the advantages of nanodrugs. It demonstrated that EGM NPs treated acetaminophen (APAP)-induced DILI by scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…And other study revealed that CP-25 concentration was higher in liver tissue compared to paeoniflorin due to its elevated oral bioavailability (Zhao et al, 2019). Research supported that there was a positive correlation between ROS elevation and inflammation related pathways activation (Brennan and Gilmore, 2018;Yunrong Yang et al, 2022). And oxidative stress was happened accompanied by excessive ROS levels, which acting as signaling molecules contributing to abnormal cell growth, metastasis, disordered function, as well as enlarged proinflammatory cytokines production, allowing inflammation to progress (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…And other study revealed that CP-25 concentration was higher in liver tissue compared to paeoniflorin due to its elevated oral bioavailability (Zhao et al, 2019). Research supported that there was a positive correlation between ROS elevation and inflammation related pathways activation (Brennan and Gilmore, 2018;Yunrong Yang et al, 2022). And oxidative stress was happened accompanied by excessive ROS levels, which acting as signaling molecules contributing to abnormal cell growth, metastasis, disordered function, as well as enlarged proinflammatory cytokines production, allowing inflammation to progress (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…This approach has shown promise in treating cancers, neurodegenerative diseases, and even lessening the occurrence of seizures ( Yang et al, 2020 ; Alrashdi et al, 2023 ). Furthermore, epigallocatechin gallate Mo nanoparticles (EGM NPs) have been shown to effectively protect against drug-induced hepatic damage ( Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%